OPTIMASI KUALITAS KEKASARAN PERMUKAAN PADA PROSES ELECTROPLATING MATERIAL SS400 MENGGUNAKAN METODE TAGUCHI - Mohammad Hartono; Hari Arbiantara Basuki; Andi Sanata (ROTOR, 2019)
Quality of product in various industries, especially in metal industry is the most attention so the product can compete and attract consumers. Surface roughness is one of the demand that must be fulfilled because it can be the initiation of cracks, especially when material receives recurring and fluctuating loading. Therefore, low surface roughness can produce a product with longer lifespan material. The goal of this study is to determine the most optimal combination of electroplating process with factors variety of voltage (volts), temperature (℃), and time of immersion (minutes) to produce a low values of surface roughness. This study uses an experimental design with Taguchi method. Contribution factors of control that produce the surface roughness values ​​were influenced significantly by control factor voltage (volts) amounted to 77.31% with an average roughness value of 1.29 μm. This is due to the increase in voltage which causes the deposition of electrolyte ions which is faster in the deposition structure of the specimen. Where as other control factors were not effected significantly on the temperature control factor amounted to 4.85% with an average roughness value of 1,32 μm. These results are possible because the temperature variations used (40℃ to 50℃) are still within the optimum operating temperature. And the other control factors is immersion time amounted to 10.13% with an average roughness value of 1,32. The result ware obtained because the length of coating time affected the quantity of deposition of nickel ions on the surface of the specimen. The result of optimal condition is the voltage level 2 (6 volts), the temperature at level 2 (45℃), and the immersion time at level 3 (25 minutes).